Protective versus Conventional Ventilation for Surgery: A Systematic Review and Individual Patient Data Meta-analysis. (July 2015) - Serpa Neto, Ary; Hemmes, Sabrine N. T.; Barbas, Carmen S. V.; Beiderlinden, Martin; Biehl, Michelle; Binnekade, Jan M.; Canet, Jaume; Fernandez-Bustamante, Ana; Futier, Emmanuel; Gajic, Ognjen; Hedenstierna, Göran; Hollmann, Markus W.; et al.
Abstract : Background: Recent studies show that intraoperative mechanical ventilation using low tidal volumes ( V T ) can prevent postoperative pulmonary complications (PPCs). The aim of this individual patient data meta-analysis is to evaluate the individual associations between V T size and positive end–expiratory pressure (PEEP) level and occurrence of PPC. Methods: Randomized controlled trials comparing protective ventilation (low V T with or without high levels of PEEP) and conventional ventilation (high V T with low PEEP) in patients undergoing general surgery. The primary outcome was development of PPC. Predefined prognostic factors were tested using multivariate logistic regression. Results: Fifteen randomized controlled trials were included (2, 127 patients). There were 97 cases of PPC in 1, 118 patients (8.7%) assigned to protective ventilation and 148 cases in 1, 009 patients (14.7%) assigned to conventional ventilation (adjusted relative risk, 0.64; 95% CI, 0.46 to 0.88; P < 0.01). There were 85 cases of PPC in 957 patients (8.9%) assigned to ventilation with low V T and high PEEP levels and 63 cases in 525 patients (12%) assigned to ventilation with low V T and low PEEP levels (adjusted relative risk, 0.93; 95% CI, 0.64 to 1.37; P = 0.72). A dose–response relationship was found between the appearance of PPC and V T size ( R 2 = 0.39) but not between the appearance of PPC and PEEP level ( R 2 = 0.08). Conclusions: These data support the beneficial effects of ventilation with use of low V T in patients undergoing surgery. Further trials are necessary to define the role of intraoperative higher PEEP to prevent PPC during nonopen abdominal surgery. Abstract : This individual patient meta-analysis of 2, 127 patients ventilated under general anesthesia for surgery from 15 randomized controlled trials shows that intraoperative ventilation with low tidal volume protects against postoperative pulmonary complications, but further trials are necessary to define the role of intraoperative higher positive end–expiratory pressure to prevent postoperative pulmonary complications after major abdominal surgery.